Efektivitas Buku Saku terhadap Pengetahuan Pengelolaan Sampah Sisa Makanan Ibu Rumah Tangga - Hawa Eqyan Shifana; Windi Wulandari (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
The management of food waste in Indonesia is a significant challenge, with food waste accounting for 39,17% of the total 36 million tons of annual waste in 2024. In Sukoharjo, food waste reaches 40.71%, far exceeding the national average, yet early surveys in Wirogunan Village showed only 12.5% of housewives had the initiative to manage it. This quantitative study with a pre-experimental one-group pre-test post-test design aims to analyze the increase in housewives' knowledge regarding food waste management through a pocketbook intervention. The population consisted of 1,617 housewives, with a sample of 55 respondents selected via simple random sampling. Data were analyzed using the Wilcoxon Signed Ranks Test. The results showed a significant increase in the average knowledge score from 85.56 at pre-test to 98.40 at post-test. Statistical analysis yielded a p-value of 0.000 (p < 0.05), indicating a significant influence of the pocketbook intervention on knowledge levels. The pocketbook, which is validated and HKI-certified, proved to be an effective educational tool due to its practical design and clear visual content. These findings suggest that structured media interventions can effectively improve domestic waste management literacy to support regional environmental policies.